Pelas trilhas da ficção: a memória invencível e a invenção do nacional no romance Viva o Povo Brasileiro - Nunes, Edeildes Sena (2010)
This study analyses the dialogue between literary from and social process in the romance Viva o povo brasileiro of João Ubaldo Ribeiro (1984) having as conductor rewritten of the literary discourse regarding the representation social-history and cultural officers of the nation. In accordance with the proposed of Stuart Hall (2006), Homi Bhabha (1998), Wolfgang Iser (1996), Luiz Costa Lima (2006), Erich Auerbach (1994) and others the literature is conceived as space of the resignation of values socially instituted with whom relates criticism and new conceptions about reality, social structure, its institutions, uses, customs and dominant representations. A methodology of research stands on reading and critical analysis of the romance based on social historical studies, of the theory and literature criticism about the subject mentioned here. The dissertation divides in to three chapters. The first describes the rewritten deconstructed of the romance, in the perspective past-modern and past-colonial; the second, centralizes in the literary strategies that the artistic transposition of the contexto historic-social and the cultural emphasizing also the relation between literature and history; the third chapter deals whit the conflicting of Brazilian people, developed interior of the order. The studies evidencing that the fictional discourse of form reveals the power which creates, dialectic guided by the fiction which intermix scenes and contra scenes of the history, of memory and the national identity.